Freshman college students' reasons for enrolling in and anticipated benefits from a basic college physical education activity class - Jeremy eLackman; Matthew Lee eSmith; Elisa Beth Hutson McNeill (Frontiers Media S.A., 2015)
Background: Given the rise in US obesity rates in adulthood, efforts are needed to assess physical activity engagement during the college years as a strategy to promote a lifetime of being physically active. This study identifies the reasons incoming college freshman enrolled in basic physical education activity courses (BPEAC) and the perceived benefits they anticipated receiving as a result of course participation. Methods: Data collected from 302 college freshmen in September 2013 were analyzed. A paper-based questionnaire was administered to 78% of BPEAC sections offered at a large Southeastern university. Frequencies were presented for all participants, which were then compared by sex and course type. Kappa statistics were calculated to examine the concordance between participants' reasons for enrolling in the course and the benefits they anticipated from course enrollment.Results: Diverse physical, mental, social, and academic reasons for enrolling in BPEAC were reported by study participants. Varied anticipated benefits from course participation were reported as well. Reported enrollment reasons and anticipated benefits differed by sex and course type. High concordance between matched enrollment reasons and anticipated benefits was observed.Conclusions: Implications highlight the need for universities to provide quality BPEAC, promote high quality instruction, and offer a wide variety of physical education courses to meet the diverse needs of students.